Pendidikan Kesehatan Hipertensi Dalam Pengelolaan Tekanan Darah pada Penderita Hipertensi Di Rt 04-06 di Desa Gembor, Kota Tangerang - Adawiyah, Siti Robeatul; Yuliyanti, Ajeng Wulan; Adinata Simas, Anggie Revaldo; Aisy, Diah Rihhadatul; Naibaho, Elria Debora; Astuti, Esthi; Suwarno, Istiani Dina; Fajriatunnisa, Nur Ilmi; Hanny, Putri Marlia; Rosianna, Rosianna; Rahayu, Suci (Universitas Mataram, 2025)
Hypertension is a condition characterized by increased blood pressure due to the heart working harder to pump blood in order to meet the body’s oxygen and nutrient needs. This condition can lead to serious complications, such as damage to the heart, nerves, and kidneys, if not properly managed. Data from RT 04, RT 05, and RT 06 in Gembor Village show that the prevalence of hypertension remains relatively high. This community aimed to enhance community knowledge and awareness regarding hypertension control through health education. The intervention consisted of blood pressure measurement, interactive health counseling, and focused group discussions (FGDs) on cardiovascular health. The results showed an increase in participants’ knowledge about hypertension and its management, as well as greater awareness of the importance of prevention and blood pressure control. This activity is expected to encourage the community to adopt a sustainable healthy lifestyle as an effort to reduce the incidence of hypertension in the area.